Restorative Justice Implementation System Prosecutor in Criminal Proceedings - Supriyadi, Munir (Jurnal Hukum Khaira Ummah, 2024)
The purpose of this research is to know and analyzing the implementation of the concept of restorative justice by prosecutors in criminal cases. In this writing, the author uses a normative legal method with research specifications in the form of descriptive analysis. The accumulation of the caseload in the courts, the prisons that are becoming full, and the little people who often fall into the error of lust, commit crimes, which they sometimes do not realize, then have to languish in prison cells for months. Because our material and formal criminal law is still oriented towards retribution for the criminal act alone and has not shifted to the act and perpetrator of the crime, let alone the paradigm of the interests of the victim. The Attorney General feels that it is time for the Public Prosecutor to capture the voice of justice in society and implement the termination of prosecution of cases that are not worthy of being brought to court. The concept of Restorative Justice comes with a paradigm that is always contrasted with retributive justice or a judicial model that is solely aimed at avenging or punishing perpetrators of criminal acts.